Penggunaan Metode Role Play dalam Meningkatkan Promosi Kesehatan terhadap Perilaku Personal Hygiene Anak Usia Sekolah - Khalilah, Nur; Nur, Mohamad; Suraying, Suraying; Hidayat, Mukhlish; Purmahardini, Nova (Jurnal Akademika Baiturrahim Jambi, 2025)
Personal hygiene is personal hygiene and health that aims to prevent disease in oneself and others. Purpose: This study is to determine the effect of health education role play method on changes in personal hygiene behavior in children. Method: in this study using Quasi experimental using the research design used is one group pre test - post test design. with data analysis using the wilcoxon test. The sample was taken with purposive sampling technique as many as 36 students from the population of all students of SD Negeri Tanjung 5 Pademawu pamekasan as many as 95 students. The research instrument used was a questionnaire as a pre-test and post-test The research instrument used was a questionnaire as a pre-test and post-test instrument, while this study used Wilcoxon test analysis with a significance of <0.05 to determine changes in knowledge, attitudes, and hygiene behaviors among elementary school children at SD Negeri Tanjung 5 Pademawu Pamekasan. Results: wilcoxon test obtained P = 0.00 means P <0.05 which means there is a significant difference in knowledge, attitudes and actions before and after the intervention, which means there is an effect of using the role play method on knowledge, attitudes and actions in personal hygiene of students at SD Negeri Tanjung pademawu Pamekasan. Conclusion: Therefore, it is necessary to conduct health education to students regarding personal hygiene, and evaluate its implementation so that it is useful to improve clean and healthy living behavior, students can be more active in increasing knowledge, attitudes and skills regarding personal hygiene so that it can be applied in everyday life